Sustaining the drive to overcome the global impact of neglected tropical diseases : second WHO report on neglected tropical diseases - World Health Organization. Dept. of Control of Neglected Tropical Diseases; Savioli, Lorenzo; Daumerie, Denis; Crompton, D. W. T. (David William Thomasson); Chan, Margaret (World Health Organization, 2013)
The second WHO report on neglected tropical diseases builds on the growing sense of optimism_x000D__x000D_ generated by the 2012 publication of the WHO Roadmap. Commitments on the_x000D__x000D_ part of ministries of health in endemic countries global health initiatives funding_x000D__x000D_ agencies and philanthropists have escalated since 2010 as have donations of_x000D__x000D_ medicines from pharmaceutical companies and the engagement of the scientific_x000D__x000D_ community. _x000D__x000D_ This report marks a new phase and assesses opportunities and obstacles in the_x000D__x000D_ control elimination and eradication of several of these diseases. Unprecedented_x000D__x000D_ progress over the past two years has revealed unprecedented needs for_x000D__x000D_ refinements in control strategies and new technical tools and protocols. The_x000D__x000D_ substantial increases in donations of medicines made since the previous report_x000D__x000D_ call for innovations that simplify and refine delivery strategies. _x000D__x000D_ However some diseases including especially deadly ones like human African_x000D__x000D_ trypanosomiasis and visceral Leishmaniasis remain extremely difficult and costly_x000D__x000D_ to treat. The control of Buruli ulcer Chagas disease and yaws is hampered by_x000D__x000D_ imperfect technical tools although recent developments for yaws look promising._x000D__x000D_ The report highlights progress against these especially challenging diseases _x000D__x000D_ being made through the development of innovative and intensive management_x000D__x000D_ strategies. _x000D__x000D_ Innovations in vector control deserve more attention as playing a key part in_x000D__x000D_ reducing transmission and disease burden especially for Dengue Chagas disease_x000D__x000D_ and the Leishmaniases. _x000D__x000D_ Achieving universal health coverage with essential health interventions for_x000D__x000D_ neglected tropical diseases will be a powerful equalizer that abolishes distinctions_x000D__x000D_ between the rich and the poor the young and the old ethnic groups and women_x000D__x000D_ and men.